2018
DOI: 10.1097/qco.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

New antibiotics for ventilator-associated pneumonia

Abstract: Newly approved and investigational drugs for the treatment of VAP are expected to offer many advantages for the management of patients with respiratory infections caused by MDR. Promising characteristics of new compounds include high activity against both methicillin-resistant Staphylococcus aureus and MDR Gram-negative bacteria and a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 45 publications
0
28
0
3
Order By: Relevance
“…A combination of other antibiotic agents (e.g., plazomicin, fosfomycin, etc.) [88] or the anti-MRSA agent with ceftazidime-avibactam is plausibly recommended to enforce control of drug-resistant VAP.…”
Section: Special Considerations About Specific Antibiotics For Hap/vapmentioning
confidence: 99%
“…A combination of other antibiotic agents (e.g., plazomicin, fosfomycin, etc.) [88] or the anti-MRSA agent with ceftazidime-avibactam is plausibly recommended to enforce control of drug-resistant VAP.…”
Section: Special Considerations About Specific Antibiotics For Hap/vapmentioning
confidence: 99%
“…Notably, avibactam is not able to inhibit strains producing metallo-β-lactamases (MBL-Class B), such as the New Delhi metallo-β-lactamase (NDM), Verona integronencoded metallo-β-lactamase (VIM) and Imipenmase (IMP), as well as many of the Class D enzymes, including Acinetobacter OXA carbapenemases. 28 However, in vitro studies suggested a synergistic effect of aztreonam combined with CAZ-AVI for MDR Enterobacteriaceae MBL producers, but this combination unfortunately is not yet commercialized. 29,30 Interestingly, CAZ-AVI has shown highly bactericidal activity in vitro against Mycobacterium avium complex and Mycobacterium tuberculosis, including MDR strains 31,32 (Tables 2 and 3).…”
Section: Caz-avi Mechanism Of Action and Spectrum Of Actionmentioning
confidence: 99%
“…При выделении в качестве возбудителя синегнойной па лочки или БЛРСпродуцирующих энтеробактерий, чув ствительных к цефтолозану/тазобактаму, доступность последнего расширит далеко небогатый на сегодняшний день выбор эффективных АМП [41]. Кроме того, пер спективой ближайшего будущего является регистрация показаний к применению данного препарата для лече ния пациентов с нозокомиальной пневмонией, когда грамотрицательные возбудители становятся доминиру ющими инфекционными агентами [42,43].…”
Section: заключениеunclassified